Modelowanie rynków lokalnych w aspektach przestrzennych - Foryś, Jerzy (Wydział Prawa i Administracji UAM, 1980)
Local markets possess a market system producing hierarchy, which is naturally formed. Identification of elements of local markets system was performed for towns of the Katowice and Bielsko-Biała voivodeships with the aid of taxonomie methods of phenomena distribution. Local markets modelling is carried out for each hierarchy level separately. Retail sales sizes of a town (systtem feature) depends on: a number of population or trade network of the town (system feature), a number of population or conditions of purchases in a supplementary region (influence of environment on markets system), distances to centres on a higher hierarchy level (markets system influence on environment), other variables, influence of which is taken into account with the aid of time variable t. Independent variables exist in the model in a double form i.e. in absolute values as well as in values weighed by distances. The obtained results are then used for the purpose of forecasting sizes of retail sales due to increase in shop space of a given local market.
Modelling Local Markets in Spatial Aspects